Publication rates of full-text journal articles converted from abstracts presented during the 22nd Turkish national urology congress - KAYALI, YUNUS; KOCAASLAN, Ramazan; KAYALI, YUNUS; TOK, Adem; TEPELER, Abdulkadir (My University, 2016)
Objective: To analyze the publication rates of full-text journal articles converted from the abstracts presented in the 22(nd) Turkish National Urology Congress in 2012. Material and methods: A total of 576 abstracts accepted for presentation at the 22(nd) Turkish National Urology Association Meeting were identified from the published abstract book. The abstracts were categorized into subsections such as endourology and pediatric urology. The subsequent publication rate for the studies was evaluated by scanning PubMed Medline. Abstracts published before the proceedings were excluded from the study. Results: The abstracts were categorized as being presented orally (n=155), by poster (n=421), or by video (n=78). Of the 28 (18.3%) of 155 oral and 34 (8.15%) of 421 poster presentations, were subsequently published in several journals until March 2015. The publication rates of the abstracts based on urology subsections were as follows: neurology (25%), andrology (18.6%), endourology (17.2%), urolithiasis (15.3%), general urology (12.5%), infectious diseases (7.14%), pediatric urology (6.25%), uro-gynecology (6.06%), reconstructive urology (5.8%), and urooncology (3.8%). The average time to publication was 11.77 (0-33) months. Conclusion: This is the first study assessing the publication rates of abstracts presented at a Turkish National Urology Congress. It reveals that more qualified randomized studies need to be done to improve the rate of publication.